Coriolus Versicolor and Ganoderma Lucidum Related Natural Products as an Adjunct Therapy for Cancers: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Zhong, Linda; Yan, Peijing; Lam, Wai Ching; Yao, Liang; Bian, Zhaoxiang (Frontiers in Pharmacology, 2019)
Background: Cancer incidence and mortality rates keep rising globally. Coriolus versicolor and Ganoderma lucidum related natural products are commonly applied as a complementary therapeutic option for different stages and types of cancers. The aim of this study is to evaluate the efficacy and safety of the products for cancer therapy. Methods: Randomized controlled trials were identified by systematic search over 7 databases from inceptions to May 10, 2019. Two independent reviewers extracted data and assessed the study quality. Mete-analyses were performed to pool hazard ratio (HR), risk ratio (RR), mean diﬀerences (MD), and 95%CI using random-effects models. The sources of heterogeneity were explored by subgroup analyses and sensitivity analyses. Publication bias was detected by Funnel plots, Begg’s test and Egger’s test. Results: 23 trials involving 4,246 cancer patients were included in this work. Coriolus versicolor and Ganoderma lucidum related natural products were significantly associated with lower risks of mortality (HR: 0.82; 95%CI: 0.72, 0.94) and higher total efficacy (RR: 1.30; 95%CI: 1.09, 1.55), but no associated with control rate (RR: 1.05; 95%CI: 0.96, 1.14) compared with control treatment. There was no significant difference between Coriolus versicolor related natural products and control treatment in the effect on relapse-free survival (HR: 1.19; 95%CI: 0.91, 1.55). Compared with control treatment, Coriolus versicolor and Ganoderma lucidum related natural products had a favourable eﬀect on elevated the levels of CD3 (MD: 9.03%; 95%CI: 2.10, 16.50) and CD4 (MD: 9.2%; 95%CI: 1.01, 17.39), but had no effect on the levels of CD8 (MD: -5.52%; 95%CI: -23.17, 12.13), CD4/CD8 (MD: 0.73; 95%CI:-0.45, 1.91) or NK(MD: 5.87%; 95%CI: -1.06, 12.8). Conclusion: In this meta-analysis, we found that Coriolus versicolor and Ganoderma lucidum related natural products might have potential benefits on the overall survival and quality of life in cancer patients.